Accounting for Peer Effects in Treatment Response - Rokhaya Dieye; Habiba Djebbari; Felipe Barrera-Osorio (Institute for the Study of Labor (IZA), 2014)
When one's treatment status affects the outcomes of others, experimental data are not sufficient to identify a treatment causal impact. In order to account for peer effects in program response, we use a social network model. We estimate and validate the model on experimental data collected for the evaluation of a scholarship program in Colombia. By design, randomization is at the student-level. Friendship data reveals that treated and untreated students interact together. Besides providing evidence of peer effects in schooling, we find that ignoring peer effects would have led us to overstate the program actual impact.
Keywords: C31; C93; I22; 330; education; social network; impact evaluation